A pilot study: Alternative biomaterials in critical sized bone defect treatment. Issue 3 (March 2018) - Tarchala, Magdalena; Engel, Victor; Barralet, Jake; Harvey, Edward J.
Abstract: Background: Critical-sized bone defects are a significant challenge with limited effective reconstructive options. The Masquelet Technique (MT) offers a solution to help restore form and function. Although this technique has produced promising results; a clear mechanism has not been determined. Theories include that the induced membrane has osteogenic potential or the membrane acts as a physical barrier to prevent fibrous tissue ingrowth. We hypothesize the induced membrane acts primarily as a physical barrier and that a synthetic non-biological membrane will allow a comparable amount of bone volume in the defect site. Methods: Ten New Zealand rabbit forelimbs (n = 10) were divided into three study groups. A critical sized defect of 3.5 cm in the ulna was created. In the control group, a traditional MT was performed (n = 4). The experimental arm varied by replacement of the PMMA with a non-porous (n = 3) or porous (150um) (n = 3) polytetrafluoroethylene (PTFE) membrane filled with allograft. Micro-CT analysis was done to compare bone volume to tissue volume ratios (BV/TV). Defect sections were examined histologically with alkaline phosphatase (ALP), tartrate-resistant acid phosphatase (TRAP) and von kossa (VK) staining. Results: MicroCT analysis comparing BV/TV between the control and experimental arms showed no difference. BV/TV of the MT was 7.77% ± 2.34 compared to porous 9.12% ± 3.66 and nonporous 9.76% ± 1.57 PTFE membranes (p1 = 0.761, p2 = 0.572, respectively). Histological sections from both samples stained for ALP and TRAP displayed osteoblastic and osteoclastic activity. There was a higher amount of ALP and TRAP positively stained cells near the native bone ends in comparison to the center of the defect, in both sample types. Conclusion and significance: Replacing the induced membrane from the MT with a synthetic PTFE membrane illustrated that the membrane acts primarily as a functional barrier. Compared to the induced membrane, the PTFE membrane was able to display similar osteointegrative properties. These results allow for future optimization of the technique with the potential to further streamline towards a single stage procedure.